2016
DOI: 10.1007/s40265-016-0545-8
|View full text |Cite
|
Sign up to set email alerts
|

Review of Eravacycline, a Novel Fluorocycline Antibacterial Agent

Abstract: Eravacycline is an investigational, synthetic fluorocycline antibacterial agent that is structurally similar to tigecycline with two modifications to the D-ring of its tetracycline core: a fluorine atom replaces the dimethylamine moiety at C-7 and a pyrrolidinoacetamido group replaces the 2-tertiary-butyl glycylamido at C-9. Like other tetracyclines, eravacycline inhibits bacterial protein synthesis through binding to the 30S ribosomal subunit. Eravacycline demonstrates broad-spectrum antimicrobial activity ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
188
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(198 citation statements)
references
References 32 publications
5
188
1
4
Order By: Relevance
“…The present studies demonstrated the activity of eravacycline against a diverse group of E. coli strains. This potent activity has been observed in previous in vitro and in vivo studies against both E. coli and methicillin-resistant Staphylococcus aureus (2,(12)(13)(14). We observed cidal activity against all isolates, and the shapes of the exposure-…”
supporting
confidence: 87%
See 3 more Smart Citations
“…The present studies demonstrated the activity of eravacycline against a diverse group of E. coli strains. This potent activity has been observed in previous in vitro and in vivo studies against both E. coli and methicillin-resistant Staphylococcus aureus (2,(12)(13)(14). We observed cidal activity against all isolates, and the shapes of the exposure-…”
supporting
confidence: 87%
“…Given this, In Vivo PK/PD of Eravacycline against Escherichia coli Antimicrobial Agents and Chemotherapy enhance activity against tetracycline-resistant bacteria (11). More recently, eravacycline, a novel fluorocycline antibiotic, was developed by a total synthetic method (12) and has been shown to be a potent translation inhibitor against strains expressing acquired tetracycline-specific resistance mechanisms (2). The present studies demonstrated the activity of eravacycline against a diverse group of E. coli strains.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…q24h, with step-down to 200 mg oral [p.o.] q12h from day 3) as noninferior to levofloxacin in complicated urinary tract infection, although revised regimens continue to merit study (10). Against this background, we tested eravacycline in vitro against circulating carbapenem-resistant Enterobacteriaceae and A. baumannii isolates from the United Kingdom and sought to define the interrelationship between eravacycline and tigecycline MICs.…”
mentioning
confidence: 99%